Identification and characterization of two new markers for differentiating fall armyworm strains across the Western Hemisphere - Rodney N. Nagoshi; Ashley E. Tessnow; Robert L. Meagher (PLoS ONE, 2026)
The fall armyworm (FAW) ( Spodoptera frugiperda (J.E. Smith)) is a major pest of corn and several other crops. Although native to the Western Hemisphere, established populations were detected in western Africa in 2016 and have since been found in most corn producing areas in the Eastern Hemisphere. FAW consists of two populations historically called “host strains” that are believed to be undergoing sympatric speciation with reproductive isolation being driven primarily by host plant use. The C- and R-strains are morphologically indistinguishable and so can only be identified by a small set of molecular markers with polymorphisms in a single locus, the Triosephosphate isomerase gene ( Tpi ), currently the most commonly used for population studies. This reliance on a single marker limits confidence in the accuracy of strain identification and the consequent extrapolations of strain characteristics, indicating a need for additional markers to test these findings. This paper describes two new strain markers that provide new genetic tools for strain analysis. The data provide support for earlier conclusions about the primacy of the Z -chromosome in strain identity, the strain divergence of the Z -chromosome as a single genetic unit and expand upon previous observations to quantify differences in how each strain is evolving. These markers will facilitate further studies on the population behavior of FAW in the Western Hemisphere and should advance our understanding of the global movements of this important agricultural pest.